Possible Association between Triphasic E.E.G. Waves and Disorder of Dopaminergic Systems - Hamoen, A. M. (1973)
In a patient probably suffering from Jakob-Creutzfeldt disease of the Jones-Nevin type and in another with a cerebral infarction treatment with amantadine (Symmetrel) 100 mg twice a day caused repetitive triphasic waves to disappear from the E.E.G. in each case. In view of these findings and the fact that some other conditions in which repetitive triphasic E.E.G. waves are a clinical feature greatly improve on treatment with levodopa, the suggestion is made that these waves result from a disorder of the dopaminergic system.